The Architectural Surfaces Characteristics of Sandy Braided River Reservoirs, Case Study in Gudong Oil Field, China - Xixin Wang; Fan Zhang; Shaohua Li; Luxing Dou; Yuming Liu; Xiaoxu Ren; Depo Chen; Wen Zhao (Geofluids)
The architecture analysis of the different orders sedimentary bodies is of great significance to the efficient development of oil and gas fields. In order to investigate the effects of the architectural interfaces on reservoir quality and heterogeneity, this study takes the Gudong oil field as a case to investigate the architectural characteristics of hierarchical bounding surfaces using detailed descriptions of core and wireline logs. Architectural models from the 7th-order to the 3rd-order are analyzed, and the developmental characteristics of the 5th-order braided river, 4th-order single sandstone, and 3rd-order accretion are summarized. The interlayer between two braided rivers is floodplain mud deposition, with poor physical properties, stable thickness, and strong blocking capacity. Two models of interlayers are found in the 4th-order deposition. The first interlayer is between the braided filling channel and midchannel bar, which is composed of generally fine-grained sediments with calcium cementation and poor physical properties. The second interlayer is a transformation belt between two midchannel bars and is generally composed of gravel-scoured deposition with penetration capability. The 3rd-order surfaces are defined as the surfaces of accretions within midchannel bars. Two models of interlayers are also found in the 3rd-order surfaces of accretions. The paleocurrent of the sandy braided river is reconstructed by synthesizing the core data, well logging data, and production performance data. A total of 1 fluvial system (7th-order), 2 compound braided rivers (6th-order), 11 braided rivers (5th-order), 41 midchannel bars (4th-order), and 96 accretions (3rd-order) are developed in the study area.